Dry premixing process for positive electrode of alkaline zinc-manganese battery and alkaline zinc-manganese battery
By adopting a dry premixing process of batch addition and stirring in the positive electrode of the alkali zinc-manganese battery, the problem of difficult to mix graphene in the cathode of the alkali zinc-manganese battery is solved, and the conductivity and high-current discharge performance of the battery are improved.
Patent Information
- Application Number
- CN202411932473.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-18
AI Technical Summary
The graphite conductive agent used in the cathode of existing alkaline zinc-manganese batteries has a low conductivity, resulting in poor electron conduction capability of the cathode, and it is difficult to achieve uniform mixing of graphene in the dry premix process, affecting battery performance.
A dry premixing process for the positive electrode of an alkali zinc-manganese battery is adopted. By adding electrolytic manganese dioxide and conductive agent in batches, the first and second stirring are mixed to improve the uniformity of carbon distribution and the dispersion effect of graphene.
It effectively improves the dispersion effect and utilization of graphene, reduces the internal resistance of the battery, and enhances the performance of high current discharge.
Smart Images

Figure CN119650575A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of batteries, and in particular to an alkaline zinc-manganese battery positive electrode dry premixing process and an alkaline zinc-manganese battery. Background Art
[0002] Primary batteries have the characteristics of low self-discharge and easy use and replacement. They are one of the most popular battery products on the market. With the miniaturization of electrical appliances, primary batteries will continue to develop.
[0003] Alkaline zinc-manganese (alkaline manganese) batteries have unique advantages among primary batteries. They are cheaper than metal lithium batteries, have a higher energy density than carbon zinc batteries, and have stronger adaptability to the environment than other primary batteries. The advent of the 5G Internet of Things era has brought new challenges to batteries, requiring larger capacity, higher safety performance, better high current performance, and longer storage life. Therefore, alkaline manganese batteries will usher in a new round of technological innovation trends.
[0004] As a traditional energy storage element, the basic structure of alkaline zinc-manganese battery is divided into anode (negative electrode), cathode (positive electrode), diaphragm, electrolyte, anode current collector and external steel shell. The cathode of alkaline zinc-manganese battery is usually composed of active material manganese dioxide, conductive agent and binder. Among them, manganese dioxide as an active material has low conductivity and the cathode has poor electron conduction ability, so the importance of conductive agent is reflected. Suitable conductive agent can effectively improve the conductivity of the cathode and reduce the internal resistance of the finished battery.
[0005] The conductive agents used in the cathode of existing alkaline zinc-manganese batteries are still based on traditional graphite, semi-expanded graphite and expanded graphite. The conductivity of these graphite conductive agents is usually 20-25S / cm, while the theoretical conductivity of graphene can reach 106S / cm. Therefore, if graphene can be applied to the cathode of alkaline zinc-manganese batteries, it will be of great significance to improve the cathode conductivity.
[0006] Dry premixing is currently the most commonly used method for mixing cathode manganese dioxide and conductive agent in alkaline zinc-manganese batteries. However, since the bulk density of graphene is generally 0.01g / cm 3 ~0.03g / cm 3 The density of graphene is hundreds of times different from that of manganese dioxide. Therefore, when the dry premixing method is used to mix the cathode manganese dioxide and the conductive agent of the alkaline zinc-manganese battery, there is a problem that graphene is difficult to mix evenly, which needs to be solved urgently. Summary of the invention
[0007] The first object of the present invention is to provide a dry premixing process for the positive electrode of an alkaline zinc-manganese battery to improve the mixing effect when graphene is used as a positive electrode conductive agent for an alkaline zinc-manganese battery. The process is beneficial to reducing the internal resistance of the alkaline zinc-manganese battery and increasing the high current discharge performance of the battery.
[0008] A dry premixing process for an alkaline zinc-manganese battery positive electrode comprises the following steps: (1) preparing conductive agent powder and electrolytic manganese dioxide powder according to the amount of positive electrode of alkaline zinc-manganese battery, wherein the conductive agent powder includes graphene powder; (2) taking a portion of the electrolytic manganese dioxide powder from step (1) and first stirring and mixing it with the conductive agent powder from step (1) to obtain a first mixed powder, wherein the portion of the electrolytic manganese dioxide powder accounts for 10 to 50% of the total amount of the electrolytic manganese dioxide powder; (3) Adding all the remaining electrolytic manganese dioxide powder except a portion of the electrolytic manganese dioxide powder in step (2) to the first mixed powder obtained in step (2), and performing a second stirring and mixing to obtain a final mixed powder.
[0009] The inventors studied the effects of adding electrolytic manganese dioxide in batches and adding conductive agents in batches on the uniformity of carbon distribution, and found that adding electrolytic manganese dioxide in batches and controlling its appropriate addition ratio can effectively improve the uniformity of carbon distribution of the final mixed powder. Based on the inventors' research results, the inventors added electrolytic manganese dioxide in two batches, and the electrolytic manganese dioxide solid powder added for the first time accounted for 10-50% of the total amount of electrolytic manganese dioxide solid powder, so that the extreme difference of carbon content at different positions in the final mixed powder obtained was less than 0.15%, which effectively improved the dispersion effect of graphene and the utilization rate of graphene. Under the condition of equal graphene addition, the dry premixing process of the present invention was used to produce the positive electrode of alkaline zinc-manganese battery and assembled into alkaline zinc-manganese battery, and the battery internal resistance was lower and the battery large current discharge performance was better.
[0010] Furthermore, the stirring time of the first stirring in step (2) is 10 to 30 minutes, and the stirring linear speed is 1 to 10 m / s.
[0011] Furthermore, the stirring time of the second stirring in step (3) is 10 to 30 minutes, and the stirring linear speed is 1 to 10 m / s.
[0012] Furthermore, the specific surface area of the graphene is greater than 20 m 2 The microstructure of the graphene can be a single layer, a few layers or multiple layers.
[0013] In order to have better conductive properties, the graphene is preferably prepared by physical exfoliation. Physical exfoliation is the main process for mass production of graphene at present, and its products have stable consistency and high conductivity.
[0014] Furthermore, the conductive agent is graphene, or a mixture of graphene and an existing conductive agent for alkaline zinc-manganese batteries. The existing conductive agent for alkaline zinc-manganese batteries uses any one of expanded graphite and flake graphite or a combination of the two. The conductive agent is graphene, which means that the conductive agent component is 100% graphene.
[0015] Furthermore, 0<the content of the graphene / (the sum of the content of the conductive agent and the electrolytic manganese dioxide)≤5%.
[0016] The second object of the present invention is to provide an alkaline zinc-manganese battery, including an alkaline zinc-manganese battery positive electrode, wherein the processing technology of the alkaline zinc-manganese battery positive electrode includes the dry premixing process of the alkaline zinc-manganese battery positive electrode described in the first object of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the SEM image of the final mixed powder obtained in Example 4.
[0018] Figure 2 This is the SEM image of the final mixed powder obtained in Example 5.
[0019] Figure 3 It is a graph showing the relationship between different proportions of graphite or graphene and resistivity. DETAILED DESCRIPTION
[0020] The following is a detailed description of the alkaline zinc-manganese battery positive electrode dry premixing process and the preferred embodiments of the alkaline zinc-manganese battery of the present invention in conjunction with the accompanying drawings.
[0021] A dry premixing process for an alkaline zinc-manganese battery positive electrode comprises the following steps: (1) preparing conductive agent powder and electrolytic manganese dioxide powder according to the amount of positive electrode of alkaline zinc-manganese battery, wherein the conductive agent powder includes graphene powder; (2) taking a portion of the electrolytic manganese dioxide powder from step (1) and first stirring and mixing it with the conductive agent powder from step (1) to obtain a first mixed powder, wherein the portion of the electrolytic manganese dioxide powder accounts for 10 to 50% of the total amount of the electrolytic manganese dioxide powder; (3) Adding all the remaining electrolytic manganese dioxide powder except a portion of the electrolytic manganese dioxide powder in step (2) to the first mixed powder obtained in step (2), and performing a second stirring and mixing to obtain a final mixed powder.
[0022] The applicant used different first addition ratios of electrolytic manganese dioxide (i.e., the proportion of a portion of electrolytic manganese oxide powder to the total amount of electrolytic manganese dioxide powder) under the same cathode formula (the conductive agent powder was composed of graphene and graphite, and the addition ratio of the graphene: the graphite: the electrolytic manganese dioxide was 95:2.5:2.5) and the same stirring conditions (the stirring time of the first stirring was 30 minutes and the stirring line speed was 10 meters per second; the stirring time of the second stirring was 30 minutes and the stirring line speed was 10 meters per second) to premix the conductive agent with the electrolytic manganese dioxide; and the carbon content of the final mixed powder was tested at different positions (5 positions). The test results are shown in Table 1 below.
[0023] Table 1
[0024] It can be seen from the test results in Table 1 that the initial addition ratio of electrolytic manganese dioxide ranges from 10% to 90%, and the final mixed powder is taken at different positions and the carbon content is tested using a carbon-sulfur analyzer. When the initial addition ratio of electrolytic manganese dioxide is below 50%, the carbon content range at different positions is less than 0.15%; when the initial addition ratio of electrolytic manganese dioxide is greater than 50%, the carbon content range at different positions is greater than 0.15%, and when the initial addition ratio of electrolytic manganese dioxide is greater than 80%, the carbon content range at different positions is greater than 0.2%. Therefore, the initial addition ratio of electrolytic manganese dioxide powder is preferably 10% to 50%, which can effectively improve the dispersion effect of graphene.
[0025] The SEM image of the final mixed powder obtained in the above comparative example 4 is as follows: Figure 1 shown.
[0026] The SEM image of the final mixed powder obtained in Example 5 is as follows: Figure 2 shown.
[0027] At the same time, the present invention also analyzes the influence of adding the conductive agent twice (the operation steps are: taking out a part from the conductive agent powder, first stirring and mixing with the electrolytic manganese dioxide powder to obtain the first mixed powder; then adding all the remaining conductive agent powder except the part of the conductive agent powder to the first mixed powder, stirring and mixing for the second time to obtain the final mixed powder) on the dispersion performance, and adopts different conductive agent first addition ratios for dry premixing. The carbon content of the final product at different positions (5 positions) is tested. The test results are shown in Table 2 below.
[0028] Table 2
[0029] From Table 2, we can see that adding the conductive agent in batches did not achieve a better dispersion effect, and the extreme difference of carbon content at different positions was above 0.2%. Because the conductive agent was added in batches, the surface energy of the carbon material (i.e., conductive agent) and the cathode material (manganese dioxide) was very different due to their different physical properties such as particle size and specific surface area. The carbon material content was low, and the overall surface energy of the material could not be neutralized during the first stirring and mixing, so the dispersion improvement effect could not be achieved.
[0030] In addition, the inventors also premixed different graphene contents (graphene contents were 0%, 1%, 3%, and 5%, respectively) according to the dry premixing process of the present application (the first manganese dioxide addition ratio was 50%) under the condition of "graphite and graphene were mixed to form a conductive agent, and the total amount of the conductive agent added was 5%". Then, an adhesive was added, and after mixing evenly, potassium hydroxide electrolyte was sprayed in. After wet mixing evenly, the mixture was rolled, granulated, and sieved, and then pressed into the positive electrode ring of No. 5 alkaline battery, assembled into No. 5 alkaline manganese battery, and the gas production was tested at high temperature and the discharge performance was tested under different discharge modes.
[0031] Gas production test: The new battery was placed at 71°C for 7 days and then taken out and placed for 24 hours. The gas production of the battery was tested using the exhaust method. The results are shown in Table 3.
[0032] Table 3
[0033] It can be seen from Table 3 that as the proportion of graphene in the conductive agent increases, the gas production also increases continuously, but the overall gas production is still very small, less than 0.2 ml, indicating that in terms of gas production, there is no safety problem in adding graphene as a conductive agent.
[0034] And the discharge performance tests under different discharge modes were carried out for Examples 6 to 9. The test batteries are all new batteries, and the discharge performance test results corresponding to "graphite 5%" (i.e., graphene is 0) are taken as the base 100%. The discharge performance test results of each embodiment are shown in Table 4. The "750 / / 150mA 0.2S / 7S 7.2S / min 1.05V discharge" in Table 4 specifically means: 750mA discharge 0.2S, 150mA discharge 7 seconds as a cycle, one cycle per minute, and a cut-off voltage of 1.05V; "3.9Ω1h / d 0.8V discharge" specifically means: 3.9Ω constant resistance discharge, one hour a day, and a cut-off voltage of 0.8V.
[0035] Table 4
[0036] It can be seen from Table 4 that: in the 750mA high current pulse discharge mode ("750 / / 150mA 0.2S / 7S 7.2S / min1.05V discharge"), adding graphene as a conductive agent can effectively improve the high current performance of the battery, with an improvement of up to 10%; in the 3.9Ω constant resistance discharge ("3.9Ω 1h / d 0.8V discharge"), adding graphene as a conductive agent can also achieve a 2% improvement.
[0037] The specific surface area of the graphene used in the present invention is greater than 20 m 2 / g.
[0038] The microstructure of the graphene can be a single layer, a few layers, or multiple layers.
[0039] In order to have better conductive properties, the graphene is preferably prepared by physical exfoliation, which is the main process for mass production of graphene and has the characteristics of stable product consistency and high conductivity.
[0040] The graphite of the present invention may be flake graphite, expanded graphite, etc. Of course, the conductive agent of the present invention may also include other common conductive agents for alkaline zinc-manganese batteries, such as carbon nanotubes and conductive carbon black.
[0041] In addition, the inventors also conducted resistivity tests on graphite and graphene in the same proportions. The test results are as follows: Figure 2 , the specific test method is as follows: Resistivity test: Take out 2 g of electrolytic manganese dioxide powder doped with different proportions of graphite or graphene, and use a YPD30S electric tablet press (produced in Tianjin) to press it into a disc with a thickness of 3 mm and a diameter of 150 mm. The tablet pressure is 10 Mpa. The pressed disc is placed in the ACCFILM resistance tester for resistance testing. The tested resistance is used to calculate the resistivity ρ according to formula I: ρ=RS / L Formula Ⅰ In formula I: R is the electrode resistance; S is the electrode surface area; L is the electrode height.
[0042] The resistivity test results are as follows: Figure 3 As shown. Figure 3 It can be seen that the resistivity of 3% graphene is 30 mΩ·cm, and the resistivity of the same proportion of graphite is about 125 mΩ·cm. Graphene has a significant advantage over graphite in reducing resistivity; but as the addition ratio increases, this advantage of graphene over graphite becomes weaker and weaker; when the addition amount of graphene is increased to 8%, the resistivity difference between the same proportion of graphene and graphite is basically the same. Based on this, preferably, 0<the content of the graphene / (the sum of the content of the conductive agent and the electrolytic manganese dioxide)≤5%.
[0043] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A dry premixing process for alkaline zinc-manganese battery positive electrode, characterized in that: The following steps are involved: (1) preparing conductive agent powder and electrolytic manganese dioxide powder according to the amount of positive electrode of alkaline zinc-manganese battery, wherein the conductive agent powder includes graphene powder; (2) taking a portion of the electrolytic manganese dioxide powder from step (1) and first stirring and mixing it with the conductive agent powder from step (1) to obtain a first mixed powder, wherein the portion of the electrolytic manganese dioxide powder accounts for 10 to 50% of the total amount of the electrolytic manganese dioxide powder; (3) Adding all the remaining electrolytic manganese dioxide powder except a portion of the electrolytic manganese dioxide powder in step (2) to the first mixed powder obtained in step (2), and performing a second stirring and mixing to obtain a final mixed powder.
2. The dry premixing process for the positive electrode of alkaline zinc-manganese battery according to claim 1, characterized in that: The stirring time of the first stirring in step (2) is 10 to 30 minutes, and the stirring linear speed is 1 to 10 m / s.
3. The dry premixing process for the positive electrode of alkaline zinc-manganese battery according to claim 1, characterized in that: The stirring time of the second stirring in step (3) is 10 to 30 minutes, and the stirring linear speed is 1 to 10 m / s.
4. The dry premixing process for the positive electrode of alkaline zinc-manganese battery according to claim 1, characterized in that: The specific surface area of the graphene is > 20 m 2 / g.
5. The dry premixing process for the positive electrode of alkaline zinc-manganese battery according to claim 1, characterized in that: The graphene is prepared by a physical exfoliation method.
6. The dry premixing process for the positive electrode of alkaline zinc-manganese battery according to claim 1, characterized in that: The conductive agent is graphene, or a mixture of graphene and an existing conductive agent for alkaline zinc-manganese batteries; the existing conductive agent for alkaline zinc-manganese batteries is either expanded graphite or flake graphite, or a combination of the two.
7. The dry premixing process for the positive electrode of alkaline zinc-manganese battery according to claim 1, characterized in that: 0<the content of the graphene / (the sum of the contents of the conductive agent and the electrolytic manganese dioxide)≤5%.
8. An alkaline zinc-manganese battery, comprising an alkaline zinc-manganese battery positive electrode, characterized in that: The processing technology of the alkaline zinc-manganese battery positive electrode comprises the dry premixing process of the alkaline zinc-manganese battery positive electrode as described in any one of claims 1 to 7.
Citation Information
Patent Citations
Positive electrode of alkaline battery and preparation method of positive electrode
CN104218229A
Semi-solid battery positive electrode material and alkaline zinc-manganese battery prepared from same
CN110739459A
Zinc-manganese dry battery and preparation method thereof
CN112467157A
Preparation device and preparation method of alkaline battery positive electrode
CN113964286A
Alkaline zinc-manganese battery
CN114388831A
Cited By
Alkali manganese button cell positive electrode powder dry manufacturing equipment and granulation process
CN120637371A